PERHITUNGAN LABA / RUGI TOKO KELONTONG DI KOTA DEPOK - Mishelei Loen (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2015)
This study examined about the calculation of income for a grocery company in the city depok. Grocery companies in the city depok majority still use the traditional system in the sales process, so that the owner of a grocery company does not do its accounting records. Grocery companies to make profits through the sales process can be said to be maximal, because of differences between the major parties as well as sales of smaller parties and the difference in rates (eg, Batak and grasslands). Researchers use a (single) sample grocery companies from 12 (twelve) prusahaan sample grocery in town depok PERINDAGKOP registered in the Office of the City of Depok.